EKSPLORASI PENERAPAN METODE QUR’ANI DAN KEDISIPLINAN IBADAH DALAM MEMBANGUN KARAKTER ISLAMI SISWA DI MADRASAH IBTIDAIYAH MIFTAHUL ULUM TUNGGAK CERME - Ilma Nabila; Nur Khosiah; A Fauzi; Rahmat Hasandi; Rahmat Bani (PT Innovative Academic Journals, 2025)
This research aims to explore the implementation of the Qur'ani method and discipline in worship in building the Islamic character of students at Madrasah Ibtidaiyah Miftahul Ulum Tunggak Cerme. The research method used is qualitative with a case study approach. Data collection was conducted through interviews, observations, and documentation. The research subjects included the head of the madrasah, teachers, and students. The results of the study show that the Qur'ani method, which consists of learning to read, memorize, and understand the Qur'an, along with the discipline of worship such as congregational prayer, remembrance (dzikr), and voluntary fasting, effectively shapes the Islamic character of students. Students who actively participate in these programs show improvements in discipline, obedience, and awareness of Islamic values. Additionally, the practice of worship discipline fosters sustainable good habits in students' lives outside the madrasah. However, challenges were identified in maintaining consistency in program implementation, particularly for students who do not live within the pesantren environment and due to limited facilities. The madrasah’s efforts to involve parents and enhance facility support are crucial steps to overcome these challenges. Overall, the implementation of the Qur'ani method and worship discipline has proven effective in building the Islamic character of students at Madrasah Ibtidaiyah Miftahul Ulum.